Change of anti-Mullerian-hormone levels during follicular phase in PCOS patients - Köninger, Angela; Koch, L.; Enekwe, A.; Birdir, C.; Kasimir-Bauer, S.; Kimmig, R.; Strowitzki, Thomas; Schmidt, B. (Gynecological endocrinology, 2015)
Anti-Mullerian-hormone (AMH) does not seem to fluctuate significantly during the menstrual cycle in healthy women. However, little is known about cycle fluctuations of AMH levels in patients with polycystic ovarian syndrome (PCOS). The purpose of this study was to examine AMH fluctuations during the follicular phase in PCOS patients receiving antiestrogens or recombinant follicle-stimulating hormone (FSH).